A educação dos leigos no reino visigodo: reflexões sobre a Vita Sancti Aemiliani = Laymen education in the Visigothic kingdom: reflection on the Vita Sancti Aemiliani - Leila Rodrigues da Silva; Rodrigo dos Santos Rainha (Universidade Estadual de Maringá, 2010)
Este artigo visa discutir aspectos da educação dos leigos no reino visigodo no século VII, tendo como pressuposto que, diante da reorganização eclesiástica em curso, o processo educacional teria se identificado com o trabalho de cristianização. Nesse sentido, compreendemos que teria se manifestado em espaços sociais variados. Para explicitar a questão, analisamos uma hagiografia produzida no século VII pelo Bispo Bráulio de Saragoça, Vita Sancti Aemiliani. Na abordagem deste documento, observamos seu caráter pedagógico, bem como traços da afirmação de um modelo educacional que valoriza demaneira singular o papel do mestre. The intention of this article is to study laymen education in the7th century Visigothic kingdom, starting from the assumption that, faced with the ecclesiastical reorganization under way, the educational process would identify with the work of Christianization. In that sense, it is understood that it would have manifested inseveral social spaces. To explain this question, we analyze a hagiography produced in the 7th century by the bishop Braulio of Saragossa, Vita Sancti Aemiliani. In investigating this document, we observe its pedagogical character, as well as traces of the affirmation of an educational model that especially values the role of master.